Pengembangan Media Pembelajaran Interaktif PETRANUM berbasis Android untuk Meningkatkan Kemampuan Numerasi Siswa Sekolah Dasar - Anggraeni, Alfina Dewi; Oktiningrum, Wuli (IAIN Kendari, 2024)
The tendency of teachers to deliver conventional learning and not utilize technology-based learning media has an impact on students' low understanding of mathematics learning material. This research aims to develop PETRANUM interactive learning media and examine the effectiveness of this media in improving the numeracy skills of grade 1 elementary school students. The research findings show that the results of material expert validation of learning media design are 97.67% which is in a very valid category. Meanwhile, the percentage of validation results from media experts is 85% in the valid category. In this way, the learning media design created meets the valid criteria and is suitable for use. The results of the large group gain test were 1.05 in the high category, meaning that the numeracy literacy abilities of grade 1 elementary school students increased after the Android-based PETRANUM interactive learning media was used in the learning process.Keywords: Android, arithmetic operations, interactive learning media